Incompetent Perforator Veins; To treat or not to treat - Thilina Gunawardena; Nalaka Gunawansa (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2019)
The role of perforator vein incompetence (PVI) in the development of venous hypertension, chronic venous insufficiency (CVI) and ulceration has been well recognized for over a century. However, while minimally invasive endovenous ablative therapies have revolutionized the management of superficial truncal vein insufficiency, the definitive indications for intervention and management of PVI still remains somewhat debatable and unclear. This review will attempt to clarify the indications for intervention as well as look at the evidence for different methods of treatment in established PVI.